Isolation, Identification and Antibiogram Pattern of Bacteria Associated with Postpartum Metritis in Dairy Cattle - Yadav , Vishal; Khandelwal, Shivali; Dholpuria, Sandeep; Purohit, Govind Narayan (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Microbial agents were isolated from forty-three clinical cases of postpartum metritis in dairy cattle from Bikaner, Rajasthan, India and their antibiogram pattern was recorded. Staphylococcus species were the most prevalent and Klebsiella species were the least prevalent. Maximum percent of uterine isolates were sensitive to Ceftiofur sodium, Ceftriaxone, Cephapirin, Cefoperazone and were resistant to Ampicillin and Amoxycillin. This analysis may help in understanding and tracking the types of microorganisms involved and the development of antimicrobial sensitivity and resistance patterns for different categories and generations of antibiotics frequently used in given geographical area related to clinical cases of metritis in dairy cattle.